Aplicación del Sonar de Barrido Lateral a la cartografía de fondos marinos. Ejemplo de la Ría de Pontevedra (Galicia, NO España). - Vilas, Federico; Durán, R.; García-gil, SOLEDAD (Journal of Iberian Geology, 2000)
Side scan sonar is used to provide a high resolution mapping of the seafloor of the Ría de Pontevedra. Sonograph analysis allows us to distinguish four backscatter patterns. Bottom samples within each pattern establish a direct relationship between backscatter and sediment texture. Sonograph correlation with land geology permit the differentiation between granitic and metamorphic basement, as well as its structural features (fractures). The side scan sonar is also used for discriminating sedimentary (megaripples) and anthropogenic features (mussel rafts, trawl-marks) and also for establishing the relationship between the hydrodynamic conditions and geomorphology of the Ría.